2022
DOI: 10.3389/fcell.2022.832114
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Mechanisms and Targeted Therapy of Pyroptosis in Central Nervous System Trauma

Abstract: Cell death can occur in different modes, ferroptosis, pyroptosis, apoptosis, and necroptosis. Recent studies have shown that pyroptosis can be effectively regulated and that like necroptosis, pyroptosis has been regarded as a type of programmed cell death. The mechanism of its occurrence can be divided into canonical inflammasome-induced pyroptosis and noncanonical inflammasome-induced pyroptosis. In the past research, pyroptosis has been shown to be closely related to various diseases, such as tumors, neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Pyroptosis is involved in the pathogenesis of various central nervous system diseases, such as cerebral hemorrhage, Parkinson's disease, and Alzheimer's disease. Intervening in pyroptosis can exert neuroprotective effects and improve disease outcomes [7]. Recent studies have shown that the levels of NLRP3 and Caspase-1 are upregulated in a PTZ mouse model, and inhibiting NLRP3 can improve seizure activity [37], indicating that pyroptosis may play an important role in the pathogenesis of epilepsy, and inhibiting pyroptosis could be a potential therapeutic approach for epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis is involved in the pathogenesis of various central nervous system diseases, such as cerebral hemorrhage, Parkinson's disease, and Alzheimer's disease. Intervening in pyroptosis can exert neuroprotective effects and improve disease outcomes [7]. Recent studies have shown that the levels of NLRP3 and Caspase-1 are upregulated in a PTZ mouse model, and inhibiting NLRP3 can improve seizure activity [37], indicating that pyroptosis may play an important role in the pathogenesis of epilepsy, and inhibiting pyroptosis could be a potential therapeutic approach for epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is involved in the pathophysiological processes of various central nervous system diseases, such as brain hemorrhage [4], Alzheimer's disease [5], and Parkinson's disease [6], and intervention in pyroptosis can improve the outcomes of these diseases [7]. Studies have shown a link between epilepsy and pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Intact cell membrane, normal nuclear morphology, atrophy of mitochondria, increased density of mitochondrial membrane, and reduced or disappeared density of mitochondrial cristae Iron accumulation and lipid peroxidation GPX4, SLC7A11, TFR1, Nrf2, NCOA4, ACSL4, FSP1 [6,7] Necroptosis Organelle swelling, loss of plasma membrane integrity, and the breakdown of cell membranes leads to the release of cell contents RIPK1, RIPK3, MLKL phosphorylation and ubiquitination, and formation of necrotic complexes in the cytoplasm RIPK1, RIPK3, MLKL [8][9][10][11][12][13] Pyroptosis Cell swelling and formation of pores in the plasma membrane Inflammasome formation, caspase and gasdermin activation and the release of numerous pro-inflammatory factors caspase-1, GSDMD [14][15][16][17] Apoptosis Nucleus fragmentation, plasma membrane blistering, cell contraction…”
Section: Ferroptosismentioning
confidence: 99%
“…Like caspase-1, activated caspase-4/5/11 cleave GSDMD to induce pyroptosis ( Shi et al, 2015 ). Notably, while caspase4/5/11 cannot process pro-IL-1β/18 directly, they can facilitate the maturation and secretion of the IL-1β/18 via the activation of the NLRP3 in an indirect way ( Humphries et al, 2018 ; Yang et al, 2022 ). The receptors in the inflammasome complex belong in most cases to the Nod-like receptor (NLR) and absent in melanoma (AIM) 2-like receptor (ALR) families.…”
Section: Overview: Pyroptosismentioning
confidence: 99%